Progressive Bilateral Ptosis in Adduction Deficit: True Internuclear Ophthalmoplegia (INO) or Pseudo-INO? Poster Presentation - Case Report - Resident - MARSHA RAYFA PINTARY; Salmarezka Dewiputri; Annisa Nindiana Pertiwi; Syntia Nusanti; Sita Paramita Ayuningtyas; Mohamad Sidik (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Bilateral INO is a rare disease caused by a lesion in the medial longitudinal fasciculus (MLF) in the pons, resulting in adduction deficit. Progression to ptosis is rare and may confuse with pseudo-INO as in ocular myasthenia gravis (OMG). This case aims to report progressive ptosis in bilateral INO that mimics pseudo-INO. Case Illustration : A 36-year-old woman complained sudden binocular diplopia 4 days before admission. Bilateral adduction deficits (-3 and -2 of right and left eye, respectively) with nystagmus were seen. There was no ptosis. The patient was diagnosed with bilateral INO. One month later, the patient returned with bilateral ptosis. The marginal reflex distance 1 (MRD1) were 0 on both eyes. Post fatigue and ice pack test showed 2mm difference of MRD1. The single fiber electromyography (EMG) result came out negative with jitter <10%. Brain MRI revealed lesions in the posterior pons and periaqueductal on the level of midbrain. Discussion : The MLF controls 6th and contralateral 3rd cranial nerve nucleus for horizontal gaze. Ptosis in INO can occurred due to central caudal subnucleus involvement in midbrain that innervates levator palpebra. The result of fatigue and ice pack test may be misleading, as those are not pathognomonic for OMG. The single-fiber EMG are valuable modalities to exclude pseudo-INO in this case. Conclusion : Progressive bilateral ptosis may occur in bilateral INO. Fatigue and ice pack test may give false- positive results leading to confusion with pseudo-INO, rather than true INO. Supporting examinations are needed to confirm the diagnosis.